Catholicism and Fascism in Europe 1918 - 1945 (Volume 26) - Nelis, Jan (Georg Olms Verlag, 2015)
The papers presented in this volume analyse the many ways in which the Vatican, national Churches and individual catholics dealt with the rise of the extreme right in Europe throughout the 1920s, 1930s and early 1940s, from the end of the First World War, arguably one of the main catalysts of European interwar fascism, to the conclusion and immediate aftermath of the Second World War. While a number of papers focus primarily on theoretical, methodological issues pertaining to the book's general theme, the majority of papers focus on either a country or region where a fascist movement or regime flourished between the wars and during the Second World War, and where there was a significant catholic presence in society. The various chapters cover almost the entire European continent - an endeavour that is unprecedented -, and they explore a wide range of relevant contexts and methodologies, thus further contributing to the general development of an interpretive 'cluster' model that incorporates a series of investigative matrixes, and that will hopefully inspire future research.